(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to identify the level of mental alertness and the accuracy of the challenge among the fencing players. In addition to identifying the type of correlation between mental alertness and the accuracy of the challenge among the fencing players. As for the hypothesis of the research, it was represented in the existence of a significant correlation between mental alertness and the accuracy of the challenge among the fencing players. As for the research sample, it was represented by the (6) fencing sport players, the mental alertness scale was distributed and the challenge accuracy test was performed on the research sample. The results showed us that the higher the mental alertness, the greater the accuracy of the challenge among the players. The most important recommendations are conducting studies similar to the current study, but on another game, paying attention to the psychological aspect and emphasizing psychological preparation before competitions